Identifying barriers to healthcare delivery and access in the Circumpolar North: important insights for health professionals. Issue 1 (1st January 2019) - Huot, S.; Ho, H.; Ko, A.; Lam, S.; Tactay, P.; MacLachlan, J.; Raanaas, R. K.
ABSTRACT: Lack of access to healthcare services for people living in the Circumpolar North may have important consequences for their health and well-being, both in terms of the actual treatment and other possible health-related consequences intertwined with their life situation. The aim of the present study was to identify the specific challenges to healthcare service delivery and access for populations in the Circumpolar North that are addressed in contemporary literature. A scoping review of literature published between 2005 and 2016 was conducted and 43 articles were selected for inclusion into the review. The review findings address 4 main themes identified in the literature: (1) the influence of physical geography, (2) healthcare provider-related barriers, (3) the importance of culture and language and (4) the impact of systemic factors. The review of the literature enabled us to identify existing gaps in both health service access and issues discussed in the available literature, particularly for informing healthcare services in the Circumpolar North, as well as point towards opportunities for future research. The thematic findings drawn from interdisciplinary and international literature inform understandings of the impact of health system barriers on healthcare services and the opportunities for Northern residents to support their own health.